Kinetic theory of magnetic absorption of laser irradiation by nanoparticles - O. Yu. Semchuk; O. O. Havryliuk; A. A. Biliuk (Хімія, фізика та технологія поверхні)
When metal nanoparticles (MNPs) are illuminated with a monochromatic laser wave, the frequency of which is far from the plasmon frequency (the frequency of plasmon resonances), under certain conditions (depending on the frequency of the wave, its polarization, the size and shape of the MNPs), absorption of light by MNPs can be dominated by magnetic absorption (absorption caused by the magnetic component of the electromagnetic field of the light (laser) wave). This work is focused on studying the features of absorption caused by the influence of the magnetic component of laser radiation. This issue is rather poorly studied for MNPs of non-spherical shape. Therefore, how the shape of the particle manifests itself in its absorption of laser radiation (laser pulses) is one of the goals of our research. In this work, we will study the features of magnetic absorption of light (laser radiation) depending on the shape of the particles. In this paper, we will investigate the influence of spheroidal MNPs on this process. Calculations will be carried out using the kinetic equation method, because we will consider the case when the size of the MNP is smaller than the length of free path of the electron in the MNP. Note that the kinetic approach makes it possible to obtain correct results for the case when the size of the particle is greater than the length of the free path. For non-spherical MNPs, we have developed a theory that makes it possible to calculate the energy of magnetic absorption by a particle when it is irradiated with laser pulses. The dependence of magnetic absorption on the ratio of the radii of curvature of spheroidal MNPs and the vector of the magnetic field of an electromagnetic (laser) wave was constructed and theoretically investigated. An interesting result is the absorption of energy by a spheroidal MNP as its disco similarity increases. We now use to estimate the relative contributions of electric We and magnetic Wm absorption to the total absorption. For example, let us take a gold MNP’s, then ?p ? 5·1015 s–1, ? ? 1013 s–1, R = 3·10–6 sm, ? ? 2·1014 s–1 (carbon dioxide laser), ?' ? –600, ?'' ? 30 we received the next ratio We/Wm ? 2. We can see that for the given set of parameters magnetic absorption is twice as large as electric. Obviously, for different parameters of the particle and a different frequency range electric absorption can be either larger or smaller than magnetic absorption. Hence, when studying the dependence of optical absorption by MNP’s on particle form, we must allow for both electric and magnetic absorption. For an asymmetric MNP’s (for example ellipsoidal particles), apart from everything else, the ratio of the electric and magnetic contributions to absorption (as fixed frequency) is strongly dependent on the degree of particle asymmetric and wave polarization.